2022
DOI: 10.1353/aad.2022.0031
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Capital in the Transition to Postsecondary Education of Students Who Are Deaf or Hard of Hearing

Abstract: Social capital can positively influence students' postsecondary aspirations and their postschool transitions to higher education and employment. Educators, families, and young people themselves can play an active role in generating and developing adolescents' social capital. A targeted focus on developing robust social capital could play an important role in the transition planning and support provided to secondary students who are deaf or hard of hearing (DHH) and contribute to their success in postsecondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Self-acceptance includes accepting one's deafness and all that goes along with being deaf or hard of hearing. Such acceptance influences how willing young people are to make use of supports specific to their deafness, for example, from teachers of the deaf during secondary school and from disability and access services in postsecondary education, and how comfortable they are advocating for their needs (Eichengreen et al, 2021;Punch & Duncan, 2022). The present study's findings indicate the importance of teachers talking about the student's deafness, both with the individual student and with their peers, and of showcasing the achievements of DHH people.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…Self-acceptance includes accepting one's deafness and all that goes along with being deaf or hard of hearing. Such acceptance influences how willing young people are to make use of supports specific to their deafness, for example, from teachers of the deaf during secondary school and from disability and access services in postsecondary education, and how comfortable they are advocating for their needs (Eichengreen et al, 2021;Punch & Duncan, 2022). The present study's findings indicate the importance of teachers talking about the student's deafness, both with the individual student and with their peers, and of showcasing the achievements of DHH people.…”
Section: Discussionmentioning
confidence: 63%
“…The present qualitative study investigated DHH university students' perceptions of how teachers, other professionals, and families could support DHH adolescents in developing social capital that would help them achieve positive postsecondary outcomes. The interview questions and discussions were based on the findings of the study's first phase, in which we identified the role that social capital had played in the participants' attainment of postsecondary education (Punch & Duncan, 2022). In this second phase, participants provided reflections, suggestions, and recommendations that in our analysis we organized under the themes of deaf connections, self-acceptance, preparation for postsecondary education and employment, fostering community connections, and family and friends.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations